Identity, Authenticity, and Humility. - Dahlstrom, Daniel O. (Aquinas Lecture in Philosophy., 2017)
An elaboration and defense of an account of the experience of self-identity that underwrites the possibility of authenticity (being true to oneself), only accessible with humility.